2009
DOI: 10.1177/1545968309341060
|View full text |Cite
|
Sign up to set email alerts
|

Combined Botulinum Toxin Type A With Modified Constraint-Induced Movement Therapy for Chronic Stroke Patients With Upper Extremity Spasticity: A Randomized Controlled Study

Abstract: Combining BtxA and mCIMT is an effective and safe intervention for improving spasticity and motor function in chronic stroke patients. The results are promising enough to justify further studies. We recommend future research to address the likely need for including rehabilitation with BtxA to improve function in patients with poststroke spasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 29 publications
(38 reference statements)
2
99
0
4
Order By: Relevance
“…Of these, 17 were excluded due to exclusion criteria: i) one trial in which post stroke spasticity was treated by botulinum toxin type B (rimabotulinumtoxinB) [21]; ii) three trial that evaluated the effect of BTX-A given early post stroke before clinically evident spasticity [22][23][24]; iii) one trial that studied the effect of BTX-A dilution and endplate-targeting in sole spastic biceps [25]; iv) five trials enrolling mixed sample of subjects with spasticity secondary to brain injury, multiple sclerosis other than stroke [9,[26][27][28][29]; v) six studies focusing the effect of BTX-A on the reduction of pain associated to spastic shoulder [30][31][32][33][34][35] and one trial that investigated the effects of BTX-A on associated reactions of spasticity [36]. The remaining 17 RTs were included [11,13,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Since one study reported secondary analysis of finding previously published, both were considered as single study, leaving 16 RTs in the analysis [13,47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 17 were excluded due to exclusion criteria: i) one trial in which post stroke spasticity was treated by botulinum toxin type B (rimabotulinumtoxinB) [21]; ii) three trial that evaluated the effect of BTX-A given early post stroke before clinically evident spasticity [22][23][24]; iii) one trial that studied the effect of BTX-A dilution and endplate-targeting in sole spastic biceps [25]; iv) five trials enrolling mixed sample of subjects with spasticity secondary to brain injury, multiple sclerosis other than stroke [9,[26][27][28][29]; v) six studies focusing the effect of BTX-A on the reduction of pain associated to spastic shoulder [30][31][32][33][34][35] and one trial that investigated the effects of BTX-A on associated reactions of spasticity [36]. The remaining 17 RTs were included [11,13,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Since one study reported secondary analysis of finding previously published, both were considered as single study, leaving 16 RTs in the analysis [13,47].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, one study investigated BTX-A plus ES compared to solely ES. The remaining three studies concerned BTX-A and physiotherapy strategies: one described the effect of combined BTX-A plus modified constraint induced therapy (mCIT) compared to BTX-A plus conventional physiotherapy [48], one study in which BTX-A plus physical therapy was compared to placebo plus physical therapy [51], and one study without placebo group that compared BTX-A plus standardized physiotherapy to group with solely standardized therapy [49,50]. In six studies, it was commonly noted that all participants received or continued a physical rehabilitation program, but the content of this was not described [38,[40][41][42][43][44].…”
Section: Associated Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45][46][47][48][49][50][51] The majority of effect sizes were close to a 1:1 relationship between the lab-based versus patient-perceived functional measures within the same study ( Figure 4). Effect sizes from studies which investigated CIMT [36][37][38]46,47 and one study that examined the effect of mirror therapy for individuals with Complex Regional Pain Syndrome 43 did not demonstrate this 1:1 relationship. Effect sizes for the perceived effect (MAL) were 1.66.2 times larger than the functional changes (measured by ARAT or Wolf) in these studies.…”
Section: Observed Changementioning
confidence: 99%
“…MAL, SIS) (n=23). The most common outcome measures used together were the MAL with the ARAT (used in 7 studies) [35][36][37][38][39][40][41] or MAL with the Wolf (used in 10 studies). [42][43][44][45][46][47][48][49][50][51] The majority of effect sizes were close to a 1:1 relationship between the lab-based versus patient-perceived functional measures within the same study ( Figure 4).…”
Section: Observed Changementioning
confidence: 99%